2018
DOI: 10.1111/tpj.13895
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Arabidopsis CARBOXYLTERMINAL DOMAIN PHOSPHATASELIKE 4 induces cytokinin‐oversensitive de novo shoot organogenesis

Abstract: De novo shoot organogenesis (DNSO) is a post-embryonic development programme that has been widely exploited by plant biotechnology. DNSO is a hormonally regulated process in which auxin and cytokinin (CK) coordinate suites of genes encoding transcription factors, general transcription factors, and RNA metabolism machinery. Here we report that silencing Arabidopsis thaliana carboxyl-terminal domain (CTD) phosphatase-like 4 (CPL4 ) resulted in increased phosphorylation levels of RNA polymerase II (pol II) CTD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Given that FLC could, in turn, also affect the expression of FT to trigger flowering, we cannot exclude that this, or other yet unknown, alternative pathways are in play in the cpl3 mutant to cause its early flowering phenotype (Shen et al ., 2022; Zhang & Shen, 2022). CPL3 belongs to the Arabidopsis CPL family (Koiwa et al ., 2002), of which all five members (CPL1‐CPL5) possess an FCP domain responsible for dephosphorylating different serine residues of the RNA polymerase II CTD (Koiwa et al ., 2004; Jin et al ., 2011; F. Li et al ., 2014; Fukudome et al ., 2014; Fukudome et al ., 2018). Within the CPL family, CPL3 is the largest protein, containing a long N‐terminal domain with a unique CES1 (capping enzyme suppressor)‐like region (Koiwa et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that FLC could, in turn, also affect the expression of FT to trigger flowering, we cannot exclude that this, or other yet unknown, alternative pathways are in play in the cpl3 mutant to cause its early flowering phenotype (Shen et al ., 2022; Zhang & Shen, 2022). CPL3 belongs to the Arabidopsis CPL family (Koiwa et al ., 2002), of which all five members (CPL1‐CPL5) possess an FCP domain responsible for dephosphorylating different serine residues of the RNA polymerase II CTD (Koiwa et al ., 2004; Jin et al ., 2011; F. Li et al ., 2014; Fukudome et al ., 2014; Fukudome et al ., 2018). Within the CPL family, CPL3 is the largest protein, containing a long N‐terminal domain with a unique CES1 (capping enzyme suppressor)‐like region (Koiwa et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…CPL3 belongs to the Arabidopsis CPL family (Koiwa et al, 2002), of which all five members (CPL1-CPL5) possess an FCP domain responsible for dephosphorylating different serine residues of the RNA polymerase II CTD (Koiwa et al, 2004;Jin et al, 2011;F. Li et al, 2014;Fukudome et al, 2014;Fukudome et al, 2018). Within the CPL family, CPL3 is the largest protein, containing a long N-terminal domain with a unique CES1 (capping enzyme suppressor)-like region (Koiwa et al, 2002).…”
Section: New Phytologistmentioning
confidence: 99%
“…We have shown that CPL4 suppresses xenobiotic stress responsive genes 21 and mediates snRNA transcription termination/3ʹ-end formation. 22 In our recent report, 23 we showed that silencing of CPL4 induces CK-oversensitive DNSO from Arabidopsis roots. DNSO from CPL4 knockdown (CPL4 RNAi ) root explants are more vigorous than wild type (WT) in standard SIM condition.…”
mentioning
confidence: 86%
“…24 Although no functional link between thalianol and DNSO has been made, the inhibitory effect of thalianol to shoot growth could be related to reduction of cell proliferation during DNSO, for example, decline in cycB expression in CPL4 RNAi after explants were transferred to low-CK-containing SIM medium. 23 Alternatively, thalianol may function as a negative feedback mechanism for DNSO. At molecular level, how CPL4 is involved in thalianol cluster regulation is still unknown, as CPL4 RNAi did not show notable transcription initiation or termination defects within the locus.…”
mentioning
confidence: 99%
“…Conversely, RNA interference could be exploited to temporarily silence suppressors of organogenesis (either by introducing chemical-inducible constructs that express antisense or hairpin templates or by transient delivery of double-stranded RNA through agroinfiltration or infection with recombinant viral vectors) because permanent gene knockouts can be detrimental to normal development and they are hard to establish in polyploid crops [ 173 , 174 , 175 ]. For example, cytokinin hypersensitivity caused by the RNAi knockdown of CARBOXYL-TERMINAL DOMAIN PHOSPHATASE-LIKE 4 ( CPL4 ) was already shown to boost de novo shoot organogenesis from root explants in Arabidopsis [ 176 ]. Next, further investigation is required to probe the role of epialleles in shaping phenotypic variation.…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%